Large‐scale enterprises, social capital and the post‐disaster development of community tourism: The case of Taoping, China. (8th February 2021) - Wu, Meiling; Gao, Xing; Cao, Mengqiu; Papa, Enrica
Abstract: This study explores how large‐scale enterprises build and mobilise social capital with intra‐ and inter‐community actors to stimulate the post‐disaster development of community tourism. Based on in‐depth interviews, this case study was conducted in Taoping, China. The findings show that large‐scale enterprises integrated bonding social capital created through engaging with Taoping villagers with bridging social capital developed through inter‐community collaborations to facilitate the post‐disaster development of community tourism. This study focuses on the dynamics of interactions between large‐scale enterprises, intra‐ and inter‐community actors. It contributes to providing a deeper understanding of the significance of large‐scale enterprises for the post‐disaster development of community tourism through the lens of social capital.